Omega-3 polyunsaturated fatty acids in supporting pregnancy and fetal development: dosing considerations - Olga A. Gromova; Ivan Iu. Torshin; Tatiana R. Grishina; Svetlana I. Maliavskaia (IP Berlin A.V., 2020)
Being complex regulators of inflammation processes omega-3-polyunsaturated fatty acids (PUFAs) are vitally important for supporting pregnancy and fetal development. Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are the most important omega-3-PUFAs. The article presents the results of a systematic analysis of 1973 studies of dose-dependent effects of DHA and EPA in nutritional support of pregnancy. The analysis results suggest that DHA/EPA donations for pregnant women are effective only in doses of at least 200 mg/day. According to the analysis results, the optimal doses of DHA/EPA are in the 400- to 800-mg/day range. The dose of omega-3-PUFA for a particular patient can be assessed by the measurement of the DHA and EPA levels in the erythrocyte membrane. To achieve specific therapeutic effects (for example, lowering triglyceride levels, therapy for postpartum depression, etc.), higher doses of omega-3-PUFAs (35 g/day) may be required. With an adequate choice of dosing regimen, DHA / EPA donations have a beneficial effect on the somatic health of women of reproductive age, help to prevent pregnancy complications and determine the child development program in the subsequent years of life. DHA/EPA drugs are effective in the adjuvant therapy of various chronic disorders.